In situ growth of Au nanoparticles on Fe2O3 nanocrystals for catalytic applications - Cao, Shao-Wen (2013)
Gold nanoparticles are successfully grown in situ on α-Fe2O3 nanocrystals through a cysteine-linked seed-planting approach followed by photo-assisted growth. The size of the gold particles on α-Fe2O3 nanocrystals can be further tuned from 2 to 20 nm by using photoinduced seed-mediation strategy. The formed Au-α-Fe2O3 hetero-nanoparticles are highly dispersible in aqueous and alcohol solvents, and capable of efficient catalysis for 4-nitrophenol reduction. In addition, they also show promoted photocatalytic efficiencies for visible-light-driven dye degradation and water oxidation due to the enhancement by surface plasmon resonance of the attached gold nanoparticles. The present strategy gives a promising way to prepare hetero-nanostructures composed by metal oxide nanocrystals and metal nanoparticles with tailorable sizes for broad applications in catalysis and photocatalysis.